Transformation of Fish Apartment into a Marine Ecotourism Village of Tegineneng, Limau District, Tanggamus Regency - Fauzi Syah Putra; Muliawati Handayani; Lalik Salistia Citra; Dona Setya; Denta Tirtana; Mestiria Harbani Sitepu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The fish apartment in Pekon Tegineneng, Limau Sub-district, Tanggamus Regency, was initially established as an artificial habitat aimed at supporting the recovery of fishery resources by protecting spawning and nursery grounds. With a 32% increase in tourist visits by 2024, the area has gradually transformed into a marine ecotourism destination involving the participation of the Tourism Awareness Group (Pokdarwis). This activity aimed to strengthen the capacity of Pokdarwis to manage conservation-based ecotourism, improve community welfare, and preserve the sustainability of the fish apartment ecosystem. The methods employed included training sessions, facilitation of ecotourism governance planning, focus group discussions (FGDs), and pilot implementation of the governance model accompanied by facilitators from the State Polytechnic of Lampung over a three-month period. The results indicate that through the integration of SWOT analysis and community empowerment, a participatory strategy for managing fish apartment-based ecotourism was developed, leading to improved management capacity, enhanced branding, and the diversification of tourism products rooted in local wisdom and environmental conservation.